Ilona Zrínyi, the symbol of freedom and courage - Csatáry György; Чотарі Юрій; Yurii Chotari (Інститут українознавства ім. І. Крип’якевича НАН України, 2020)
Abstract. The article describes the important moments of life and active political activity of one prominent female fi gure in the history of Transcarpathian region – Countess Ilona Zrínyi, who lived in Mukachevo in the 17th century and protected Mukachevo Castle from the Austrian invaders. The Countess’ personality is also shown as a symbol of freedom and courage, which was especially emphasized during the siege of Mukachevo Castle by the Habsburgs in the second half of the 17th century (1685–1688). The article analyses eleven original letters written by Ilona Zrínyi before the siege of Mukachevo Castle. They testify to the connection between the Countess and the leadership of the Uzhanskyi and Berezhskyi counties (present-day territory of Transcarpathian region). They are stored in the Berehove Branch of the State Archives of Transcarpathian Oblast. These letters are important sources of evidence of Europe-wide history of our region. In the fi nal part of the present article we have collected evidence based on press material and documents in the State Archives of Transcarpathian Oblast describing the so-called «Ilona-days», i.e. celebrations commemorating the personality of the great political and historical fi gure, Countess Ilona Zrínyi. All the offi cial documents provide proof of the fact of how local people of Uzhanskyi and Berezhskyi counties (present-day Transcarpathia) loved and deeply respected the countess for her courage to fi ght for freedom against the Habsburgs, for her never-ending feeling of responsibility for her nation, and attentive care for her own motherland. During the siege of Mukachevo Castle with Ilona Zrínyi had her son, Ferenc Rákóczi II with her, who was still a child. The siege at that time taught the future leader of the liberation struggle of 1703–1711 to be courageous, and to love his motherland. Further research into sources related to Ilona Zríny’s activities may continue in the archives of Hungary and other countries as she unsuccessfully sought to form an international anti-Habsburg coalition.

Резюме. Описано важливі моменти життя й активної політичної діяльності однієї з видатних жіночих постатей історії Закарпатської обл. – графині Ілони Зріні (Ilona Zrínyi), яка проживала в ХVII ст. у м. Мукачево та захищала місцевий замок від австрійських окупантів. Також показано особистість графині як символ свободи і мужності, що було особливо продемонстровано під час облоги Мукачівського замку Габсбургами у другій половині ХVII ст. (1685–1688). Проаналізовано 11 оригінальних листів, які написала Ілона Зріні ще до облоги замку, і вони свідчать про зв’язки між графинею та керівництвом Ужанського й Березького комітатів (тепер – територія Закарпатської обл.). Вказано, що вони зберігаються у Берегівському відділенні Державного архіву Закарпатської обл. Зазначено, що ці листи – важливі джерела-докази всеєвропейської історії нашого регіону. Зібрано докази на основі матеріалів преси та документів у Державному архіві Закарпатської обл., котрі описують т. зв. «Ілонині дні», тобто урочистості, які вшановують особу великого політичного й історичного діяча – графиню Ілону Зріні. Констатовано, що всі офіційні документи свідчать про те, як місцеві жителі Ужанського та Березького комітатів (тепер – Закарпаття) любили й глибоко поважали графиню за її мужність у боротьбі за свободу проти Габсбургів, за її нескінченне почуття відповідальності за свою націю та уважну турботу про власну батьківщину. Встановлено, що під час облоги Мукачівського замку з Ілоною Зріні перебував ще маленьким Ференц Ракоці ІІ (Ferenc Rákóczi II) – тодішня облога навчила майбутнього керівника визвольної боротьби 1703–1711 рр. сміливості, любові до батьківщини. Констатовано, що подальше дослідження джерел, які стосуються діяльності Ілони Зріні, може продовжитись в архівах Угорщини й інших країн, оскільки вона намагалася створити міжнародну антигабсбургську коаліцію.
Ілона Зріні, символ свободи та відваги
Keywords: Countess Ilona Zrínyi; Mukachevo Castle; Transcarpathian history